Governance of the Expansion Area in Bintauna Village, Bintauna District, North Bolaang Mongondow Regency - Cisilia Korompot (Asian Journal of Applied Business and Management, 2023)
This study aims to find out about the Governance of Expansion Areas in the Bintauna Village, Bintauna District, North Bolaang Mongondow Regency. This type of research is Qualitative. This type of research is descriptive. Data collection techniques use instruments in the form of observation, interviews, and literature studies. The results of this study indicate that communication between sub-districts, sub-districts and districts has been running but not optimal, so that the regulations for the Bintauna sub-district are not in accordance with procedures because the sub-district rules are still attached to sub-districts such as villages, which causes the implementation of services to not run optimally because there are still many things that need to be fixed, especially regarding the rules because in fact the ward has its own government but in its implementation it is still attached to the supervision of the sub-district. It is suggested that it is necessary to make improvements in all aspects such as communication, village regulations, and implementation of services so that the program can run optimally.